2016
DOI: 10.1093/toxsci/kfw180
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Critical Period for the Developmental Neurotoxicity of Low-Level Tobacco Smoke Exposure?

Abstract: Secondhand tobacco smoke exposure in pregnancy increases the risk of neurodevelopmental disorders. We evaluated in rats whether there is a critical period during which tobacco smoke extract (TSE) affects the development of acetylcholine and serotonin systems, prominent targets for adverse effects of nicotine and tobacco smoke. We simulated secondhand smoke exposure by administering TSE so as to produce nicotine concentrations one-tenth those in active smoking, with 3 distinct, 10-day windows: premating, early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…These results are in accordance with previous studies of our group and with studies that show that exposure to tobacco smoke during brain development can affect the central nervous system. Exposure to tobacco smoke extract during gestational period of Sprague-Dawley rats decreased nicotinic and serotonin receptors in different brain regions (Slotkin et al, 2017). In addition, postnatal exposure to tobacco smoke leads to impairment in the myelination, learning, and memory, and induces oxidative stress and lower brain-derived neurotrophic factor (BDNF) and synaptic proteins levels (Stangherlin et al, 2009;Lobo-Torres et al, 2012;Torres et al, 2015a,b).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous studies of our group and with studies that show that exposure to tobacco smoke during brain development can affect the central nervous system. Exposure to tobacco smoke extract during gestational period of Sprague-Dawley rats decreased nicotinic and serotonin receptors in different brain regions (Slotkin et al, 2017). In addition, postnatal exposure to tobacco smoke leads to impairment in the myelination, learning, and memory, and induces oxidative stress and lower brain-derived neurotrophic factor (BDNF) and synaptic proteins levels (Stangherlin et al, 2009;Lobo-Torres et al, 2012;Torres et al, 2015a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for early gestational exposure to an extract from tobacco smoke to alter neurodevelopmental outcomes was recently reported in a Sprague-Dawley rat model (Slotkin et al, 2016). In this study, pregnant dams were exposed to tobacco smoke extract by infusion minipumps for the first ten days of gestation, resulting in perturbations to both the cholinergic and serotonergic systems in the postnatal offspring (Slotkin et al, 2016).…”
Section: Early Gestational Maternal Smokingmentioning
confidence: 90%
“…In this study, pregnant dams were exposed to tobacco smoke extract by infusion minipumps for the first ten days of gestation, resulting in perturbations to both the cholinergic and serotonergic systems in the postnatal offspring (Slotkin et al, 2016).…”
Section: Early Gestational Maternal Smokingmentioning
confidence: 99%
“…Yet, the same group separately observed that ETS influenced synaptic organization within the hippocampus, an area with no direct cerebellar feedback [19] . Recently researchers at Duke reported that the PFC was vulnerable in utero to doses of ETS condensate, which they directly contrasted with nicotine alone [6,20] . They determined that ETS condensate was more bioactive than nicotine in driving synaptic abnormality in the PFC.…”
mentioning
confidence: 99%